Impacts of a metropolitan-scale freeway expansion program on air pollution and equity. (September 2021) - Kocak, Talha K.; Gurram, Sashikanth; Bertini, Robert L.; Stuart, Amy L.
Abstract: Context: To enable human mobility, economic vitality, and population well-being in growing cities, well-planned transportation infrastructure is essential. However, transportation systems can also have detrimental impacts on health and equity, including through increased air pollution and its unequal social distribution. Aims: This study focuses on estimating air quality and equity impacts of an ongoing large-scale metropolitan transportation program (known as "Tampa Bay Next"). Our objective was to characterize and quantify the air pollution levels and population exposures resulting from an interstate freeway expansion planned under Tampa Bay Next, which includes added toll lanes. Methods: We estimated changes in individual human exposures to oxides of nitrogen (NOx ) due to the proposed freeway changes, using an integrated suite of high-resolution models for travel demand, emissions, pollutant dispersion, and exposure. Inequity in the distribution of exposures among racioethnic and income groups was also estimated using a few measures of inequality (the subgroup inequality index (SII), the comparative environmental risk index, and the toxic demographic quotient index). Findings: The planned freeway expansion was estimated to slightly decrease the daily NOx emissions (by 5.6 mg/m, p = 4×10 −16 ), ambient concentrations (by 0.02 μg/m 3, p = 2×10 −4 ), and individual exposures (by 0.2 μg/m 3, p = 2.2×10 −16 ) on average, while increasing exposure densities during peak periods in areas surrounding downtown Tampa. Group-average exposures also decreased for all population subgroups under the planned expansion scenario. However, disparities in exposure increased for the black (ΔSII = 1.3×10 −3 for the 90th percentile exposure level) and the below-poverty (ΔSII = 4.6×10 −3 ) groups. Conclusions: Results suggest that a detailed analysis of exposures may be needed to ensure large-scale transportation improvement programs reduce inequity, even when average impacts on air quality and exposures are positive or neutral. Highlights: The roadway expansion decreased total emissions and average NOx concentrations. The roadway expansion decreased average population and subgroup exposures. Concentrations and individual exposures increased near the proposed lanes. Disparities in exposure by race and income were exacerbated by the proposed lanes. Refined analyses may be needed to ensure equitable exposure outcomes.